TRANSIENT FREQUENCY STABILITY ASSESSMENT OF THE INTERCONNECTED SOUTH SULAWESI POWER NETWORK - Efendi, Khorul Fahmi; Lomi, Abraham; Muljanto, Widodo Pudji; Wartana, I Made; Krismanto, Awan Uji (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2024)
The power system consists of interconnected generation, transmission, and load centres, forming a complex electrical network called a grid. One of the significant challenges in power systems is ensuring stability—the system's ability to return to regular or stable operation (steady state) after experiencing significant disturbances such as generation loss, switching operations, sudden load changes, or faults like short circuits. Transient analysis plays a crucial role in determining the appropriate relay operation scheme, critical disconnection time for circuit breakers, and the transfer capability between systems, all of which must be optimised to maintain stability. This study simulates and analyses the frequency transient stability to assess system reliability during disturbances of the 150 kV South Sulawesi interconnected system. The study also determines the Critical Clearing Time (CCT) necessary to achieve the stable conditions of the interconnected system. The simulation is tested on the South Sulawesi interconnected system. The analysis results show frequency drops of about 0.0397% at GI Bantaeng and 0.0401% at the GI Punagaya bus, PLTU Jeneponto 1, and PLTU Jeneponto 2.